The Rio de Janeiro Low Carbon City Development Program : A Business Model for Green and Climate-Friendly Growth in Cities - World Bank (Washington, DC, 2014)
The Rio de Janeiro Low Carbon City Development Program is an ISO-certified framework and set of comprehensive requirements to help the city to plan, implement, monitor, and account for low carbon investments and climate change mitigation actions across all sectors in the city over time. The Program will enable the city to plan and implement the mitigation actions needed to achieve its city-wide mitigation goals, as well as credibly and transparently demonstrate the achievement of those goals through diligent monitoring and accounting of the actions taken. This issue of Directions in Urban Development describes the context underlying the development of the Program in Rio, and the key components of such an ISO-certified program including roles and responsibilities, planning and evaluation, and the program process.